Head gardeners - Edwards, Ambra; Hopkinson, Charlie (London : Pimpernel Press, 2017)
Ambra Edwards and Charlie Hopkinson explore, in words and pictures, the lives, visions and achievements of fourteen very different head gardeners.
Introduction: On behalf of gardeners -- The naturalist: Ned Price, The Weir, Herefordshire -- The generous gardener: Fergus Garrett, Great Dixter, East Sussex -- A survivor's tale: Paul Pulford, Queen Elizabeth Hall, London -- But is it art?: Mick Evans, Packwood House, Warwickshire -- Gardening like a cow: Beatrice Krehl, Waltham Place, Berkshire -- Is a man up to the job?: Troy Scott Smith, Sissinghurst Castle, Kent -- Space for thought: Lucille Savin, Merton College, Oxford -- What's the big idea?: Alistair Clark, Garden of Cosmic Speculation, Dumfries -- Mending what is broken: Carol Sales, Headley Court, Surrey -- Planting for posterity: Andrew Woodall, Broughton Grange, Oxfordshire -- The show must go on: Michael Walker, Trentham Gardens, Staffordshire -- Mission impossible: Martin Ogle, Lowther Castle, Cumbria -- Partners in perfectionism: Jim Buckland & Sarah Wain, West Dean Gardens, West Sussex -- Visitor information.
Includes index.
boek
Keywords: Gardeners -- Great Britain; Gardeners; Great Britain; Biographies; Biographies